INKARNASI KRISTUS SEBAGAI POLA HIDUP ORANG PERCAYA MENURUT FILIPI 2:5-8 - Susanto Dwiraharjo (Manna Rafflesia, 2025)
The concept of incarnation has given rise to much theological discussion. Each of them has a different argumentative background. This is motivated by different methods and approaches. This article attempts to convey the concept of incarnation with a biblical approach. The method used is exegesis. This is an attempt to find the truth according to what God's Word meant. It is hoped that through this article the truth about the biblical concept of incarnation can be found, and can be a reference in various discussions related to the theme.